1989
DOI: 10.1002/jmor.1052010207
|View full text |Cite
|
Sign up to set email alerts
|

Failure to turn eggs during incubation: Development of the area vasculosa and embryonic growth

Abstract: Effect of turning of the egg during incubation on development of the area vasculosa of the chick embryo was investigated. The size of the area vasculosa was determined by two methods: direct measurement with calipers and measurement of a template cut from the eggshell by use of an automatic surface area recorder. The effects of turning and additionally the effects of lowered temperature (36°C) on both growth of the area vasculosa by day 7 and embryo growth by day 14 of incubation were investigated. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…It is required that poultry eggs are rotated during the development stages. Any mistakes during this process may cause of a decrease in oxygen uptake, delayed extra embryonic membranes, vascularization and embryonic development [3,4] . Generally, it is known that the yield of incubation rate of waterfowl is lower than that of chicken.…”
Section: Introductionmentioning
confidence: 99%
“…It is required that poultry eggs are rotated during the development stages. Any mistakes during this process may cause of a decrease in oxygen uptake, delayed extra embryonic membranes, vascularization and embryonic development [3,4] . Generally, it is known that the yield of incubation rate of waterfowl is lower than that of chicken.…”
Section: Introductionmentioning
confidence: 99%
“…Rate of growth of the area vasculosa of the yolk sac membrane during the ®rst third of incubation was slower in unturned eggs (Deeming, 1989b). Later in development the pattern of growth of the chorioallantoic membrane is disrupted in unturned eggs (Tullett and Deeming, 1987).…”
Section: Egg Turning and The Avian Embryomentioning
confidence: 93%
“…Later in development the pattern of growth of the chorioallantoic membrane is disrupted in unturned eggs (Tullett and Deeming, 1987). Failure to turn eggs also affects the volume of the allantois and amnion and slowed the rate of embryonic growth (Tazawa, 1980;Tullett and Deeming, 1987;Deeming, 1989aDeeming, , 1989bDeeming, , 1989cDeeming, , 1989dDeeming, , 1991. For various reasons, the protein content of amniotic¯uid is reduced in unturned eggs (Deeming, 1991) because less albumen proteins move through the sero-amniotic connection (Hirota, 1894;Deeming, 1991).…”
Section: Egg Turning and The Avian Embryomentioning
confidence: 99%
See 1 more Smart Citation
“…Baggott et al (2002) suggested that in unturned eggs this 'depleted layer' would reduce the sodium available for ion transport by endodermal cells and thus decrease SEF formation. Alternatively, or in addition, it was suggested that the lower rate of expansion of the area vasculosa present in unturned eggs (Deeming, 1989a) might also reduce SEF mass. However, neither hypothesis provides a complete explanation of the occurrence in turned eggs of additional fluid at the time of maximum SEF mass (Babiker and Baggott, 1992).…”
Section: Introductionmentioning
confidence: 99%